Metal Doped Porous Carbons for Use in Energy Applications: A Review - Findlay, Elliot (2022)
With a rapidly growing world population and rising global temperatures, a need for a green energy store to replace fossil fuels is more necessary than ever. Many methods and materials have been put forward as candidates, such as Li-ion batteries, supercapacitors, solar-powered cells, and hydrogen fuel cells. However, many of these methods are not fully optimised and cannot realistically compete with fossil fuels. Supercapacitor electrodes made from activated carbon or graphene often lack a large enough capacitance to compete with Li-ion batteries as an efficient energy store, and transition metal oxides have been known to increase capacitance of various materials. This review compares and contrasts the capacitive abilities of various transition metal oxide-doped activated carbon and graphene composites, for use as supercapacitor electrodes, in comparison to their pristine counterparts. Another major problem with new energy stores is the efficient and safe storage of molecular hydrogen, for a potential hydrogen economy. This review explores the use of various metals as dopants for increasing the hydrogen uptake capacities of activated carbons, as well as other carbon based hydrogen stores.